2006
DOI: 10.1177/205873920601900111
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia Pneumoniae in Asymptomatic Carotid Atherosclerosis

Abstract: We evaluated, in 415 patients with asymptomatic carotid atherosclerosis: (i) the prevalence of C pneumoniae DNA in atherosclerotic carotid plaques and peripheral blood mononuclear cells (PBMC); (ii) the distribution of C pneumoniae in atherosclerotic carotid plaques and PBMC from the same patients; (iii) the correlation between circulating anti-chlamydial antibodies and the presence of C pneumoniae DNA. Overall, 160 atherosclerotic carotid plaques and 174 PBMC specimens from patients with asymptomatic carotid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Indeed, the detection of chlamydial DNA by polymerase chain reaction (PCR) has contributed significantly in demonstrating the association of C. pneumoniae with atherosclerotic cardiovascular disease (7,(24)(25)(26)(27). Therefore, we believe that direct detection of C. pneumoniae in tumor lung tissue is needed to support its involvement in the pathogenesis oflung cancer.…”
mentioning
confidence: 99%
“…Indeed, the detection of chlamydial DNA by polymerase chain reaction (PCR) has contributed significantly in demonstrating the association of C. pneumoniae with atherosclerotic cardiovascular disease (7,(24)(25)(26)(27). Therefore, we believe that direct detection of C. pneumoniae in tumor lung tissue is needed to support its involvement in the pathogenesis oflung cancer.…”
mentioning
confidence: 99%
“…chronic diseases has re-emerged. The involvement of C. pneumoniae in the pathogenesis of chronic extrapulmonary diseases is supported by direct detection of chlamydial DNA in cerebrospinal fluid of multiple sclerosis patients, brains of affected Alzheimer subjects, and in atherosclerotic lesions (4)(5)(6)(7). Of these chronic diseases, the strongest association has been with atherosclerosis in animal models, which provide causal evidence (8) and by direct detection of the microorganism in atherosclerotic lesions.…”
mentioning
confidence: 77%
“…Current opinion is that C. pneumoniae infection is implicated in several chronic extrapulmonary diseases such as atherosclerosis, multiple sclerosis, and Alzheimer's disease (1)(2)(3)(4)(5). However, association of C. pneumoniae with multiple sclerosis and Alzheimer's disease remains highly controversial, whereas that with atherosclerosis has gained much support over the past years.…”
mentioning
confidence: 99%
“…In atherosclerosis, the involvement of e. pneumoniae, a respiratory pathogen, has been supported by seroepidemiology, identification of the microorganism within atheroma by immunochemistry and electron microscopy, and direct detection of chlamydial DNA within atheroma by polymerase chain reaction (PCR) (13)(14)(15). Several in vivo studies have shown that e. pneumoniae contributes to exacerbation of lesions in hyperlipidaemic animal models, suggesting thatthis microorganism is aco-risk factor with hyperlipidaemia (15).…”
Section: The Involvement Ofc Pneumoniae In Cardiovascular Diseasementioning
confidence: 99%